Rural and urban encounters in Reijo Kela’s choreographies "Ilmari’s Ploughed Field" (1988) and "Cityman" (1989) - Kukkonen, Aino (Nordic Theatre Studies, 2016)
Since the early 1980s, the solo performances of Reijo Kela (b. 1952) have brought original perspectives to Finnish dance, particularly in terms of how he wanted to dance in close proximity to the spectator and how the lines between art-forms were blurred. In his first large-scale site-specific works, Ilmari’s Ploughed Field (Ilmarin kynnös, 1988) and Cityman (1989), he dealt with the relationship between dance, site, and changing Finnish society. They occurred in the heart of rural and urban life: one, in an abandoned field in Suomussalmi Eastern Finland and the other, in the busiest shopping area of the capital. In my article I examine how and what kind of ideas of countryside and city Kela’s work manifest. What kind of cultural images they represent? And how they were received at the time of their premiere? The theoretical approach includes Rosalyn Deutsche’s ideas of assimilative space and disturbance of space.